Aerogels based on reduced graphene oxide/cellulose composites: Preparation and vapour sensing abilities - Chen, Yian; Poetschke, Petra; Pionteck, Juergen; Voit, Brigitte; Qi, Haisong (Nanomaterials, 2020)
This paper reports on the preparation of cellulose/reduced graphene oxide (rGO) aerogels for use as chemical vapour sensors. Cellulose/rGO composite aerogels were prepared by dissolving cellulose and dispersing graphene oxide (GO) in aqueous NaOH/urea solution, followed by an in-situ reduction of GO to reduced GO (rGO) and lyophilisation. The vapour sensing properties of cellulose/rGO composite aerogels were investigated by measuring the change in electrical resistance during cyclic exposure to vapours with varying solubility parameters, namely water, methanol, ethanol, acetone, toluene, tetrahydrofuran (THF), and chloroform. The increase in resistance of aerogels on exposure to vapours is in the range of 7 to 40% with methanol giving the highest response. The sensing signal increases almost linearly with the vapour concentration, as tested for methanol. The resistance changes are caused by the destruction of the conductive filler network due to a combination of swelling of the cellulose matrix and adsorption of vapour molecules on the filler surfaces. This combined mechanism leads to an increased sensing response with increasing conductive filler content. Overall, fast reaction, good reproducibility, high sensitivity, and good differentiation ability between different vapours characterize the detection behaviour of the aerogels.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Aerogel; Cellulose; Conductive polymer composite; Reduced graphene oxide; Vapour sensor